2018
DOI: 10.7150/jca.24236
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vascularity observed using contrast-enhanced 3D ultrasonography and pathological changes in patients with hepatocellular carcinoma after sorafenib treatment

Abstract: Aim: The aim of this study was to compare vascularity observed using contrast-enhanced 3D ultrasonography and pathological changes in human hepatocellular carcinoma (HCC) and surrounding non-tumorous areas after sorafenib treatment.Materials and methods: Twelve patients with HCC were enrolled in this clinical study. The maximum tumor diameter as measured using sonography ranged from 15 to 33 mm (mean, 24.0 mm; SD, 5.7 mm). Assessments using contrast-enhanced (0.2 mL of Sonazoid suspension; Daiichi Sankyo, Toky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although the therapeutic evaluation of sorafenib for HCC using CEUS has been reported, there are only a few reports on LEN. 10 , 11 , 12 , 13 We hypothesized that blood flow evaluation by CEUS is useful in predicting the therapeutic effect of LEN. In this study, we investigated whether the therapeutic effect of LEN could be accurately assessed using the minimally invasive measurement of blood flow in HCC during the early stages of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although the therapeutic evaluation of sorafenib for HCC using CEUS has been reported, there are only a few reports on LEN. 10 , 11 , 12 , 13 We hypothesized that blood flow evaluation by CEUS is useful in predicting the therapeutic effect of LEN. In this study, we investigated whether the therapeutic effect of LEN could be accurately assessed using the minimally invasive measurement of blood flow in HCC during the early stages of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…With the administration of an ultrasonographic contrast agent, CE-US brings a higher signal-to-noise ratio and a higher sensitivity for slow flow than traditional B-mode US (9). CE-US has been widely used in many fields including hepatocellular carcinomas (HCC), breast cancers, and colorectal cancers (10)(11)(12). Previous studies have evaluated the efficacy of chemotherapy in different cancers using CE-US, and reported that CE-US could be useful in evaluating tumor progression by detecting changes in tumor vascularity (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…CE-US has been widely used in many fields including hepatocellular carcinomas (HCC), breast cancers, and colorectal cancers (10)(11)(12). Previous studies have evaluated the efficacy of chemotherapy in different cancers using CE-US, and reported that CE-US could be useful in evaluating tumor progression by detecting changes in tumor vascularity (10)(11)(12). Kudo et al compared B-mode US with CE-US for the surveillance of HCC and recommended CE-US as a useful detection method for HCC (13).…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib inhibits the RAS/RAF/MEK/ERK signaling pathway by inhibiting the activity of RAF, thereby directly suppresses tumor cell proliferation, and induces apoptosis of cancer cells [16]. On the other hand, SOR can also inhibit neovascularization and cut off the supply of tumor nutrition, thereby inhibiting tumor growth and metastasis [17]. And SOR as a chemical drug has a broad-spectrum antitumor effects and is commonly used in the treatment of liver and kidney cancer.…”
Section: Introductionmentioning
confidence: 99%